Colchicine inhibits ROS generation in response to glycoprotein VI stimulation - G. J. Pennings (Nature Portfolio, 2021)
Abstract Colchicine inhibits coronary and cerebrovascular events in patients with coronary artery disease (CAD), and although known to have anti-inflammatory properties, its mechanisms of action are incompletely understood. In this study, we investigated the effects of colchicine on platelet activation with a particular focus on its effects on activation via the collagen glycoprotein (GP)VI receptor, P2Y12 receptor, and procoagulant platelet formation. Therapeutic concentrations of colchicine in vitro (equivalent to plasma levels) significantly decreased platelet aggregation in whole blood and in platelet rich plasma in response to collagen (multiplate aggregometry) and reduced reactive oxygen species (ROS) generation (H2DCF-DA, flow cytometry) in response to GPVI stimulation with collagen related peptide-XL (CRP-XL, GPVI specific agonist). Other platelet activation pathways including P-selectin expression, GPIIb/IIIa conformational change and procoagulant platelet formation (GSAO+/CD62P+) (flow cytometry) were inhibited with higher concentrations of colchicine known to inhibit microtubule depolymerization. Pathway specific mechanisms of action of colchicine on platelets, including modulation of the GPVI receptor pathway at low concentrations, may contribute to its protective role in CAD.